Political Connections and Tax Avoidance in the Indonesian Banking Industry - Patlial Hunaida; Elin Erlina Sasanti (PT FORMOSA CENDEKIA GLOBAL, 2025)
The purpose of this study is to examine the effect of political connections on tax avoidance, with size, profitability, and leverage as control variables. The population in this study consists of 47 banking companies listed on the Indonesia Stock Exchange (IDX), and the sample was selected using purposive sampling. Based on predetermined criteria, 31 companies were chosen as the sample, resulting in 155 observations. The sample size was determined using the Central Limit Theorem, which states that a minimum of 30 samples is required to achieve a normal distribution curve. The data analysis technique used in this study is multiple linear regression analysis using SPSS software. The results indicate that, partially, political connections have an effect on tax avoidance. However, size, profitability, and leverage do not have an effect on tax avoidance.